2008
DOI: 10.1016/j.mvr.2007.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Human postmortem brain-derived cerebrovascular smooth muscle cells express all genes of the classical complement pathway: A potential mechanism for vascular damage in cerebral amyloid angiopathy and Alzheimer's disease

Abstract: Deposition of amyloid around blood vessels, known as cerebral amyloid angiopathy (CAA), is a major pathological feature found in the majority of Alzheimer's disease (AD) cases, and activated complement fragments have been detected on CAA deposits in AD brains. In this study, we demonstrate for the first time that human cerebrovascular smooth muscle cells (HCSMC) isolated from cortical vessels derived from postmortem brains can express mRNAs for complement genes C1qB, C1r, C1s, C2, C3, C4, C5, C6, C7, C8 and C9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 47 publications
(51 reference statements)
1
18
0
Order By: Relevance
“…In another study, human cerebrovascular SMCs expressed mRNA of many complement cascade genes including C1QB, C1R, C1S, C2, C3 and C4 from the classical pathway. 38 Our results demonstrated the presence of the complement proteins C2, CFH, C3, and transcription factor STAT5A in the cells of the aortic wall. Although CFB-mRNA was expressed in AAA tissues, CFB protein was not detectable in aortic wall tissue.…”
Section: Discussionsupporting
confidence: 56%
“…In another study, human cerebrovascular SMCs expressed mRNA of many complement cascade genes including C1QB, C1R, C1S, C2, C3 and C4 from the classical pathway. 38 Our results demonstrated the presence of the complement proteins C2, CFH, C3, and transcription factor STAT5A in the cells of the aortic wall. Although CFB-mRNA was expressed in AAA tissues, CFB protein was not detectable in aortic wall tissue.…”
Section: Discussionsupporting
confidence: 56%
“…Three such genes were present in component 1. Immune function, especially the complement system, related to amyloid-beta clearance (Guerreiro et al, 2010; Kolev et al, 2009) and expressed in cerebrovascular smooth muscle (Walker et al, 2008), is suggested by ATF7, CFB, C2, SKIV2L, C6orf10 and C6orf15 (Li et al, 2006; Veerhuis, 2010). These genes support the known role of the complement system in LOAD pathogenesis (van Es and van den Berg, 2009), while adding new gene candidates, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…CFH was also reported as a blood biomarker for AD disease progression (Hye et al 2006). Complement factors are associated with senile plaques and play a central role in the inflammation process in brains of AD patients (Walker et al 2008;Yasojima et al 1999). SerpinG1 Ser/Cys protease inhibitor and Serpin G1 plasma protease C1 inhibitor control the activity of the complement proteases (Murray-Rust et al 2009).…”
Section: Discussionmentioning
confidence: 99%